2018
DOI: 10.1097/mpg.0000000000001719
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Proteases, Antiproteases, and Bioactive Proteins From Mother's Breast Milk to the Premature Infant Stomach

Abstract: Most human milk proteases are active in milk but not at preterm infant gastric pH. Only cathepsin D and plasmin have potential to continue degrading milk proteins within the preterm infant stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
(53 reference statements)
3
29
0
1
Order By: Relevance
“…Our previous study found that cathepsin D and plasmin from human milk were still active in the preterm stomach at two hours postprandial. Our recent research also demonstrated that pepsin/cathepsin D activities and proteolysis increased from human milk to the preterm infant stomach at two hours postprandial.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our previous study found that cathepsin D and plasmin from human milk were still active in the preterm stomach at two hours postprandial. Our recent research also demonstrated that pepsin/cathepsin D activities and proteolysis increased from human milk to the preterm infant stomach at two hours postprandial.…”
Section: Discussionmentioning
confidence: 94%
“…The results are expressed as units per millilitre, where one unit of protease activity is the amount of enzyme that generates 1 μ mol of L‐tyrosine per min. For protease activity in human milk, the assay buffer (initial at pH 1.3) was adjusted with 1 M sodium hydroxide to pH 6.4 to approximate average milk pH from this study and our previous article . For protease activity in the gastric samples, the assay buffer was adjusted to pH 4.5 with 1 M sodium hydroxide to approximately match the average gastric sample pH of this study.…”
Section: Methodsmentioning
confidence: 99%
“…No study has compared the survival of Igs in the stomach or intestine between preterm and term infants. Our recent studies demonstrated that preterm infants partially degrade IgA but not IgG and IgM in the stomach [ 21 , 22 ]. A few studies have measured the survival of milk Igs to infant stool [ 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human milk feedings were delivered via the nasogastric tubes over 30 min. Two hours after the initiation of feeding, 2 mL of each preterm and term infant’s gastric contents were collected in a syringe back through the feeding tube via suction as previously described in our studies [ 21 ]. Gastric samples were aspirated at 2 h postprandial to obtain samples that represented a compromise between when adequate sample remained recoverable from the stomach and a maximum feasible length of gastric digestion time had passed based on gastric emptying times [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation